Women’s Fiqih (Haid, Nifas, And Istihadhah) on Reproductive Health - Ai Umir Fadhilah (Proceeding International Conference on Religion, Science and Education, 2023)
Almost all Postgraduate students at UIN Sunan Kalijaga Yogyakarta know about Women’s Fiqh (Menstruation, Postpartum, and Istihadhah) and its relation to reproductive health. The purpose of this study was to analyze the understanding of postgraduate students at UIN Sunan Kalijaga Yogyakarta regarding women’s Fiqh (menstruation, childbirth, and istihadhah) and its relation to reproductive health. An understanding of women’s fiqh related to women’s bleeding (dima’ al-mar’ah) is very important for both men and especially women to have. The understanding of postgraduate students regarding menstrual blood, childbirth, and istihadhah, the majority is still at a moderate level. They can only define and know the difference in the time of discharge and the color of the blood, but they do not yet know and define the legal implications for women who experience bleeding regarding the implementation of worship, and its relation to women’s reproductive health. Of the several factors that affect one’s understanding, five main factors greatly influence students’ understanding of menstrual blood, postpartum, and istihadhah, namely experience, gender, education, environment, and information media.